Explaining disparities in transitions among visual-functioning states. (1st July 2019) - Liew, Hui
Abstract : Visual impairment is one of the most common disabilities among older adults and the majority of the visually impaired and blind worldwide are those aged 50 and older. This study aims to examine whether transitions across different visual-functioning states (good and better to poor) among older adults in the United States reflect the processes associated with double-jeopardy intersectionality, cumulative advantage (disadvantage), persistent inequality and age-as-leveller. The empirical work of this study is based on the 2002–14 Health and Retirement Study (HRS). Multistate life tables are used to assess the aim of the study. Findings from multistate life tables reveal higher transition probabilities associated with vision deterioration among females, black people, Hispanic people and those with less than a four-year degree. Findings provide support for both the intersectionality hypothesis in conjunction with the cumulative advantage (disadvantage) and persistent inequality hypothesis. Targeted interventions that detect visual loss and prevent vision impairment as well as the provision of appropriate and accessible refraction and surgical services should begin early on in life and should continue to focus on the specific needs of ethnic minorities, females and those with low education. Understanding how individuals move through different visual-functioning states and identifying the risk factors for poor vision are relevant to many policy concerns that seek to reduce the disease burden or health consequences associated with visual impairment.